Schaum's 3000 solved problems in chemistry - Goldberg, David E. (Schaum's solved problem series, 1987)
Compatible with any classroom text, Schaum's Solved Problem Guides let you practice at your own pace and remind you of all the important problem-solving techniques you need to remember--fast! And Schaum's are so complete, they're perfect for preparing for graduate or professional exams.